Exploring Networks of Interaction at the Iron Age Site of Mtanye, South Western Zimbabwe - Scholfield, Jordan Ryan (Department of Archaeology, 2020)
Networks of interaction as well as community formation have been widely researched within Southern Zambezian archaeology of the early second millennium A.D. Despite this, research into these communities is often asymmetrical with objects delegated a passive role in the formation of not only networks of interaction but also socio-material development. Further, research tends to focus on society as the source of action in these processes. Using the site of Mtanye, the aim of this study is to create a relational ontology in which agency is distributed among heterogenous entities. Moreover, this study attempts to demonstrate how networks of interaction might have shaped this community. Mtanye is a Leopard’s Kopje phase 2 site with stratified Transitional K2 (1200-1250 A.D.) and Mapungubwe (1250-1300) deposit. This site has further been placed into the wider conventional narrative as being evidence for the expansion of the Mapungubwe state. In order to recreate the networks of interaction that were present at Mtanye, Actor-Network Theory informed in part by the ethno-historical record was enlisted. The results of this study show that Mtanye has hill occupation, stone walling and access to prestige goods, characteristics conventionally not ascribed to periphery sites. Further, the results of this study suggest that it is more prudent to view the socio-material development of Mtanye, not in terms of the political or economic expansion of a hegemonic power but rather as a product of heterogeneous networks of interaction. This study may further provide a framework for understanding socio-material development and networks of interaction during the early second millennium A.D. in Southern Zambezia.